Role of Transmembrane Domains of Hepatitis B Virus Small Surface Proteins in Subviral-Particle Biogenesis - Siegler, Vera D. (American Society for Microbiology, 2013)
The hepatitis B virus (HBV) surface proteins not only are incorporated into the virion envelope but in addition form subviral particles (SVP) consisting solely of surface proteins and lipids. Heterologous expression of the small HBV envelope protein S produces secreted spherical SVP 20 nm in diameter, with approximately 100 S molecules per particle. The pathway leading from the initial S translation product as a multispanning transmembrane protein to the final SVP is largely unknown. To investigate the role of the four transmembrane domains (TM) of S in this process, we introduced mutations in these regions and characterized their effects on SVP formation in transfected Huh7 cells. We found that the insertion of one amino acid in the center of the α-helix of TM1 or the exchange of TM1 with a heterologous TM blocked SVP release and SVP formation by coexpressed wild-type S chains in a transdominant negative fashion. Surprisingly, this effect was partially neutralized when the mutations were expressed in the background of the HBV surface protein M, suggesting that mutations in TM1 could partially be complemented by the pre-S2 domain. The exchange of TM2 with heterologous TMs that form α-helices of the same lengths was also incompatible with SVP formation. However, these mutants no longer blocked SVP formation by coexpressed wild-type S. We conclude that TM2 is essential for the stable assembly of S chains by establishing intramembrane interactions.